2001
DOI: 10.1007/s100960100546
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Chromogenic Medium for the Isolation and Presumptive Identification of Salmonella Species from Stool Specimens

Abstract: The performance of BBL CHROMagar Salmonella (Becton Dickinson, France), a new selective chromogenic medium for the isolation and presumptive identification of Salmonella spp., was evaluated. On this medium, which is a modification of CHROMagar Salmonella (CHROMagar Microbiology, France) with enhanced selectivity, the colonies of Salmonella are stained in mauve (rose-violet), while those of other organisms appear in blue-green or are not stained by any of the chromogens of the medium. The medium was evaluated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 14 publications
1
22
1
1
Order By: Relevance
“…Salmonella taramasında kullanılmak üzere Salmonella'ya özgü enzimleri saptayabilecek kromojenik substratlar içeren besiyerleri geliştirilmiştir 6 . Bu besiyerleri ile yapılan çalışmalarda diğer konvansiyonel besiyerleri ile kıyaslandığında doğrulama için gereken biyokimyasal ve serolojik testlerle birlikte gereken sürenin yaklaşık olarak 24 saat kısaldığı gösterilmiştir 7 . Bu besiyerleri kullanılarak Salmonella türlerinin tanısında yük-sek oranda duyarlılık ve özgüllük sağlandığı, ayrıca tanının konması için gereken sürenin azalmasının yanısıra yapılan maliyet analizinde de kullanılan besiyerleri ve teknisyen zamanı hesaplandığında maliyetin de %26 azaldığı gösterilmiştir 8 .…”
Section: Introductionunclassified
“…Salmonella taramasında kullanılmak üzere Salmonella'ya özgü enzimleri saptayabilecek kromojenik substratlar içeren besiyerleri geliştirilmiştir 6 . Bu besiyerleri ile yapılan çalışmalarda diğer konvansiyonel besiyerleri ile kıyaslandığında doğrulama için gereken biyokimyasal ve serolojik testlerle birlikte gereken sürenin yaklaşık olarak 24 saat kısaldığı gösterilmiştir 7 . Bu besiyerleri kullanılarak Salmonella türlerinin tanısında yük-sek oranda duyarlılık ve özgüllük sağlandığı, ayrıca tanının konması için gereken sürenin azalmasının yanısıra yapılan maliyet analizinde de kullanılan besiyerleri ve teknisyen zamanı hesaplandığında maliyetin de %26 azaldığı gösterilmiştir 8 .…”
Section: Introductionunclassified
“…Eigner et al tested BBL with stool samples and found a sensitivity of 85% and a specificity of 99% after 48 h of incubation of direct plates (5). In two other studies, BBL and SM were compared using stock isolates and stool samples, respectively (2,4).…”
mentioning
confidence: 99%
“…The selective agents used in these agars include dyes, antibiotics, and bile salts (7). Differentiation of most salmonellae from other organisms usually relies on the visualization of simple biochemical features such as the production of hydrogen sulfide or the nonfermentation of lactose (2,3,6,16; D. E. Post, Folio LT0435A [1997], Oxoid, Ltd., Basingstoke, United Kingdom). These media are useful for the confirmation of suspect colonies but most are highly nonspecific, mainly due to Proteus and Citrobacter strains from the normal flora, which closely resemble Salmonella strains.…”
mentioning
confidence: 99%
“…These media are useful for the confirmation of suspect colonies but most are highly nonspecific, mainly due to Proteus and Citrobacter strains from the normal flora, which closely resemble Salmonella strains. Such suspect colonies must be differentiated further by biochemical or serological tests before a final result is obtained (5,6,10,20). Due to high rates of false-positive results, screening of stool samples for Salmonella becomes labor-intensive, with additional costs for subsequent identification (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation